What would encourage help-seeking for memory problems among UK-based South Asians? A qualitative study. Issue 9 (11th September 2015) - Mukadam, Naaheed; Waugh, Amy; Cooper, Claudia; Livingston, Gill
Abstract : Objectives: People from Minority Ethnic groups tend to present late to dementia services, often in crisis. Culture-specific barriers to help-seeking seem to underlie this. We sought to determine these barriers to timely help-seeking for dementia among people from South Asian backgrounds and what the features of an intervention to overcome them would be. Study design: Qualitative study to delineate barriers to and facilitators of help-seeking for South Asian adults with dementia through focus groups and individual interviews. Setting: Community settings in and around Greater London. Participants: To achieve a maximum variation sample, we purposively recruited 53 English or Bengali speaking South Asian adults without a known diagnosis of dementia through community centres and snowballing. Results: Participants ranged in age from 18 to 83 years, were mostly female and were 60% Bangladeshi. We recruited people from different religions and occupational backgrounds and included those with experience of caring for someone with dementia as well as those without this experience. Participants identified four main barriers to timely diagnosis: barriers to help-seeking for memory problems; the threshold for seeking help for memory problems; ways to overcome barriers to help-seeking; what features an educational resource should have. Conclusions: We have identified the features of an intervention with the potential to improve timely dementia diagnosis in South Asians. The next steps are to devise and test such an intervention.